FAKTOR-FAKTOR YANG MEMPESNGARUHI KOMITMEN ORGANISASI KARYAWAN - Yupiter Gulo (Jurnal Bisnis dan Akuntansi, 2013)
The aim of this study id to analyze the influence of job satisfaction, employees employment, and job stress on organizational commitment. The data was collected by distributing questionnaires to the respondents on general division. Questionnaires distributed to 58 respondents. The findings can be summarized as follows. First, job satisfaction (X1) has an influence on organizational commitment. Second, employees employment (X2) has an influence on organizational commitment. And third, job stress (X3) has no influence on organizational commitment.